2015
DOI: 10.1038/ismej.2015.178
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in a honey bee pathogen: first report of a third master variant of the Deformed Wing Virus quasispecies

Abstract: Treatment of emerging RNA viruses is hampered by the high mutation and replication rates that enable these viruses to operate as a quasispecies. Declining honey bee populations have been attributed to the ectoparasitic mite Varroa destructor and its affiliation with Deformed Wing Virus (DWV). In the current study we use next-generation sequencing to investigate the DWV quasispecies in an apiary known to suffer from overwintering colony losses. We show that the DWV species complex is made up of three master var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
208
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(213 citation statements)
references
References 59 publications
4
208
0
1
Order By: Relevance
“…However, a 5’-terminal stretch of 10 nucleotides was missing from Kakugo virus (DWV-A, AB070959) and at least 21 nucleotides were missing from all other DWV-A genomes and Varroa destructor virus 1 (DWV-B, AY251269, Fig 2B). A length difference of 14 nucleotides was observed, when comparing DWV-A 1414 (KU847397) to the recently published genomic sequence of DWV-C (ERS657949) [27]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a 5’-terminal stretch of 10 nucleotides was missing from Kakugo virus (DWV-A, AB070959) and at least 21 nucleotides were missing from all other DWV-A genomes and Varroa destructor virus 1 (DWV-B, AY251269, Fig 2B). A length difference of 14 nucleotides was observed, when comparing DWV-A 1414 (KU847397) to the recently published genomic sequence of DWV-C (ERS657949) [27]. …”
Section: Resultsmentioning
confidence: 99%
“…Iflaviruses are members of the order Picornavirales with a Picornavirus-like genome organization and particle morphology [14]. DWV is separated into the three master variants DWV-A, -B and -C [27]. Master variant A contains the classical DWV strains [28] and Kakugo virus [29], which are responsible for elevated colony mortality [18].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, DWV-infected bees started to forage at an earlier age and showed reduced lifespans and total activity spans than control bees. Finally, next-gen sequencing demonstrated that the DWV strain we used for inoculation belonged to the type B DWB master variant [52], which has recently been found to be an emergent, more virulent strain of the DWV virus [25] that currently appears to be the most common strain in Britain [25]. The fact that our DWV lysate was prepared from a randomly selected sample of bees with overt DWV infection symptoms suggest that this strain is now also common in Continental Europe.…”
Section: Discussionmentioning
confidence: 98%
“…The amount of DWV injected was estimated at 1.2 Â 10 4 -4.6 Â 10 5 DWV copies per bee, and was aimed at mimicking infection loads reported for bees with covert infections (1.4 Â 10 3 -2.4 Â 10 9 copies per bee, [51]). Based on Illumina ultrahigh throughput sequencing, the DWV strain used for inoculation was determined to belong to the type B DWV master variant [52], which has recently been found to be an emergent, slightly more virulent strain of the DWV virus [25] that is currently also the most common strain in Britain [25] (for details, see the electronic supplementary material).…”
Section: (C) Controlled Infectionmentioning
confidence: 99%
“…In addition, DWV Type C variant is distinct from types A and B. Type C had not recently emerged, but rather is an established DWV variant (Mordecai et al, 2016).…”
Section: Dwv Which Causes Asymptomatic Chronic Infectionsmentioning
confidence: 99%